Effect of Vitamin D on Fasting Blood Sugar and HbA1c in Type 2 Diabetes Mellitus Patients - Rabab Zehra; Zareen Naz; Samina Mohyuddin; Saima Zainab; Aarfa Amjad; Ittafaq Hussain (Journal of Aziz Fatimah Medical and Dental College)
ABSTRACT: Objective: To evaluate the impact of vitamin D supplementation on fasting blood sugar & HbA1c in Type-2 diabetes mellitus patients. Methodology: This was an analytical case control study and was carried out by the Pharmacology Department at the Basic Medical Sciences Institute (BMSI, JPMC) with the collaboration of Diabetic OPD, JPMC, Karachi for the duration of 6 months. In this study 80 patients were selected by non-probability purposive sampling method and open EPI 3.01 version was used to estimate the sample size. Results: The study revealed that pre and post plasma vitamin D proportions in the intervention group were significant (P<0.001) as compared to the group labeled as control which did not show any difference at the end of study (P=0.16). However, there was an insignificant relationship between Vit D and HbA1c with no improvement observed in glycemic control (P=0.74) or HbA1c levels (P=0.20) in the intervention group. Conclusion: According to the study's findings, vitamin D addition has improved plasma vitamin D3 levels and improved insulin sensitivity in patients with T2DM. The current analysis did not find a significant contribution to reducing HbA1c or enhancing glycemic control in individuals with T2DM.